Faktor-faktor yang Mempengaruhi Holding Period Saham - Yudhistira Ardana; Tiara Novia Fatrin; Wulandari Wulandari (Benefit: Jurnal Manajemen dan Bisnis, 2018)
Stocks are an investment that many investors choose because they are able to provide an attractive rate of return. Holding period is a period that indicates the length of this study was to determine the factors that affected the holding period of shares partially on the companies listed into to LQ45 index. This study used a descriptive method, with the purposive sampling technique and it obtained 21 companies as the research sample. The result of the research showed that the market value and the trading volume were partially significant to the holding period of stock with  and sig value was smaller than 0,05 (sig 0,05) that was 0,000 and 0,005, while the bid-ask spread, variance return, and dividend payout ratio partially had no significant effect on the holding period of stock with the value of   and the sig value was greater than 0,05 (sig 0,05) that was equal to 0,414, 0,706, and 0,673. The value of the adjusted r square (R²) of 0,381 or 38,1% indicated the the bid-ask spread, the market value, the trading volume, the variance return, the dividend payout ratio could explain the holding period of 38,1%, while the remaining 61,9% was explained by other variables outside the study.